Meningkatkan Hasil Belajar Siswa SMA Pada Materi Transformasi Geometri Melalui Model Pembelajaran Kooperatif Berbasis Information, Communication and Technology - Diah Prawitha Sari; Hujairah Hi. Muhammad; Isman M. Nur; Rusmin R. M. Saleh (Jurnal Ilmiah Wahana Pendidikan, 2022)
The aims of this research are as follows: (a) to find out how student learning outcomes are when studying geometric transformation material applied through information, communication and technology-based cooperative learning methods. (b) to find out whether the use of information, communication and technology-based cooperative learning methods can improve student learning outcomes in studying geometric transformation material. (c) to find out whether there is an increase in student learning outcomes between cooperative learning methods based on information, communication and technology in studying transformation geometry material. This research is a One-Group Pretest-Posttest Design study which uses one class by applying cooperative learning methods based on information, communication and technology. The subjects in this study were 24 students of class XII IPA1. Based on the results of the study it can be concluded that:(a) student learning outcomes on geometric transformation material by applying cooperative learning methods based on information, communication and technology obtain an average of 75.79. (b) the use of information, communication and technology-based cooperative learning methods can improve student learning outcomes in geometric transformation material. (c) this shows that cooperative learning methods based on information, communication and technology can improve student learning outcomes in geometric transformation material.